Nutrition, physical activity, and quality of life among students of the Faculty of Education at Milagro State University: a cluster analysis - Robalino Muñiz, Gustavo David; González Barona, Viviana Beatriz; Robalino Muñiz, Rosa Claudiana (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The aim of this study was to analyze the relationship between eating habits, physical activity, and perceived quality of life in university students. The sample consisted of 200 randomly selected students between the ages of 18 and 30. Data collection took place in classrooms. Three main instruments were administered: the WHOQOL-BREF questionnaire to measure quality of life; a brief food frequency questionnaire to record weekly consumption of fruits, vegetables, and ultra-processed foods; and a weekly physical activity log in minutes. Anthropometric measurements were also calculated. The results revealed three profiles: a high-risk cluster (35%), characterized by high BMI, low fruit and vegetable consumption, high intake of ultra-processed foods, and low physical activity; an intermediate cluster (40%), with mixed habits and average quality of life; and a healthy cluster (25%), comprised of students with better eating habits, higher levels of physical activity, and higher perceived quality of life. These findings highlight the need to implement health promotion programs within the university context, aimed at strengthening healthy eating habits and increasing physical activity.